Impact Study of Foreign Direct Investment on Carbon Dioxide Emission, Economic Growth, Trade Openness for India following ARDL Approach - Sharmiladevi, J. C. (International Journal of Energy Economics and Policy, 2024)
Foreign Direct Investment (FDI) is instrumental in increasing growth and development in many countries. The development outcomes of FDI must also be analysed, considering the long-term holistic implications of economic growth and environmental implications. Environmental consequences of FDI need to be analysed to better understand the developmental potentials of FDI. The objective of this study is to analyse the equilibrium relationship among carbon dioxide emission, inward FDI, trade openness, and economic growth considering India by using an autoregressive distributed lag model. This model overcomes the effect of endogeneity and indicates that there is a strong cointegrating relation between all the variables with significant long-run effects for economic growth and trade openness and insignificant results with carbon dioxide emission and inward FDI.